2012
DOI: 10.1007/s00109-012-0881-4
|View full text |Cite
|
Sign up to set email alerts
|

A molecular mechanism underlying ovarian dysfunction of polycystic ovary syndrome: hyperandrogenism induces epigenetic alterations in the granulosa cells

Abstract: The objective of this study was to explore whether hyperandrogenism induces epigenetic alterations of peroxisome proliferator-activated receptor gamma 1 (PPARG1), nuclear corepressor 1 (NCOR1), and histone deacetylase 3 (HDAC3) genes in granulosa cells (GCs) of polycystic ovary syndrome (PCOS) women and whether these alterations are involved in the ovarian dysfunction induced by hyperandrogenism. Thirty-two infertile PCOS women and 147 infertile women with tubal blockage were recruited. PCOS women were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 32 publications
2
98
0
2
Order By: Relevance
“…Thus, the constant stimulation of androgens induces changes in ARs or even induces epigenetic changes, leading to ovarian dysfunction in PCOS. 24 In relation estradiol in a previous study we also obtained higher levels on PCOS group, results which meet the current immunohistochemical findings, given that the CYP1A1 enzyme that catalyzes the formation of estrogens from androgens showed greater reactivity in the PCOS group. CYP19A1 (aromatase) is normally present in granulosa cells, whereas in ovaries belonging to the PCOS group we found both immunoreactivity in granulosa cells and in the interstitial cells, which may explain the increase in estrogens.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, the constant stimulation of androgens induces changes in ARs or even induces epigenetic changes, leading to ovarian dysfunction in PCOS. 24 In relation estradiol in a previous study we also obtained higher levels on PCOS group, results which meet the current immunohistochemical findings, given that the CYP1A1 enzyme that catalyzes the formation of estrogens from androgens showed greater reactivity in the PCOS group. CYP19A1 (aromatase) is normally present in granulosa cells, whereas in ovaries belonging to the PCOS group we found both immunoreactivity in granulosa cells and in the interstitial cells, which may explain the increase in estrogens.…”
Section: Resultssupporting
confidence: 90%
“…It is believed that the theca interna cells that produce androgens act in a paracrine manner in granulosa cells. 24 Another function would be to modulate the signaling of follicle stimulating hormone (FSH) through the androgen receptors (ARs) in granulosa cells to amplify the cAMP concentration. Thus, the constant stimulation of androgens induces changes in ARs or even induces epigenetic changes, leading to ovarian dysfunction in PCOS.…”
Section: Resultsmentioning
confidence: 99%
“…The ovarian morphology assessed by ultrasound in the controls was normal for every patient. The long agonist protocol for controlled ovarian hyperstimulation (COH) and the collection of follicular fluids and GCs, obtained by follicular aspiration from women undergoing oocyte retrieval for IVF, were performed as described (25). All patient studies were approved by the Ethics Committee of the Women's Hospital, School of Medicine, Zhejiang University.…”
Section: Methodsmentioning
confidence: 99%
“…TT levels in serum were measured after exaction (26) using CLIA (Roche). TT, SHBG, E 2 levels in follicular fluids were detected as described (25). FAI was calculated as TT divided by SHBG × 100 (27).…”
Section: Measurement Of Hormonesmentioning
confidence: 99%
“…As early as 2003, it was ever suggested that even mild forms of hyperandrogenism must be considered seriously and dysregulations of the steroidogenic pathway and ovarian abnormalities must be evaluated carefully to determine the risk of functional ovarian hyperandrogenism of PCOS (Cetinkaya et al, 2003). The follicular hyperandrogenism may induce the epigenetic alterations of PPARG1, NCOR1 and HDAC3 in the ovarian granulosa cells, which may be involved in the underlying mechanism of the ovarian dysfunction in hyperandrogenism PCOS women (Qu et al, 2012). These results indicate that it is through regulating PPARG1 and HDAC3 expression levels in the ovaries that CHM significantly alleviates hyperandrogenism of PCOS rats induced by testosterone propionate.…”
Section: Discussionmentioning
confidence: 99%